(untitled) (Medicina y Seguridad del Trabajo, 2023)
Objective: To determine job satisfaction and the level of knowledge about postural hygiene as factors associated with prolonged disability in low back pain. Methods: Analytical cross-sectional study in patients with temporary work disability due to low back pain, two groups were integrated, patients with prolonged disability and patients with non-prolonged disability. The sample size was 120 per group. Job satisfaction was evaluated using the adapted instrument based on the s21/26 and S4/82 questionnaire, for postural hygiene the Borrás postural hygiene questionnaire was used. Statistical analysis included t student, Mann Whitney and Chi2. Results: No significant association was found between prolonged disability and job satisfaction. In the group with prolonged disability, 42.5% reported being quite satisfied, and in the group without prolonged disability, the prevalence was 35.0% (p=0.154). In the group with prolonged disability, the low level of knowledge about postural hygiene is 87.5% and in the group without prolonged disability, the percentage is 68.5%, a statistically significant difference (p=0.000). Conclusion: Job satisfaction is not a factor associated with prolonged disability due to low back pain, the level of knowledge about postural hygiene is a factor associated with prolonged disability due to low back pain.